Evidence for a Role for Interleukin-17, Th17 Cells and Iron Homeostasis in Protective Immunity against Tuberculosis in Cynomolgus Macaques - Wareham, Alice S. (Public Library of Science, 2014)
Tuberculosis (TB) remains a major global public health problem. The only vaccine, BCG, gives variable protection, especially in adults, so several new vaccines are in clinical trials. There are no correlates of protective immunity to TB; therefore vaccines progress through lengthy and expensive pre-clinical assessments and human trials. Correlates of protection could act as early end-points during clinical trials, accelerating vaccine development and reducing costs. A genome-wide microarray was utilised to identify potential correlates of protection and biomarkers of disease induced post-BCG vaccination and post-Mycobacterium tuberculosis challenge in PPD-stimulated peripheral blood mononuclear cells from cynomolgus macaques where the outcome of infection was known. Gene expression post BCG-vaccination and post challenge was compared with gene expression when the animals were naïve. Differentially expressed genes were identified using a moderated T test with Benjamini Hochberg multiple testing correction. After BCG vaccination and six weeks post-M. tuberculosis challenge, up-regulation of genes related to a Th1 and Th17 response was observed in disease controllers. At post-mortem, RT-PCR revealed an up-regulation of iron regulatory genes in animals that developed TB and down-regulation of these genes in disease controllers, indicating the ability to successfully withhold iron may be important in the control of TB disease. The induction of a balanced Th1 and Th17 response, together with expression of effector cytokines, such as IFNG, IL2, IL17, IL21 and IL22, could be used as correlates of a protective host response.